A Novel Technology-Enhanced Internalized Stigma and Shame Intervention for HIV-Positive Persons With Substance Use Disorders. Issue 1 (February 2020) - Batchelder, Abigail W.; Moskowitz, Judith T.; Jain, Jennifer; Cohn, Michael; Earle, Maya A.; Carrico, Adam W.
Abstract: Internalized stigma, shame, and other negative self-conscious emotions are inadequately addressed barriers to HIV-related self-care, particularly among people actively using substances. Innovative approaches are needed to optimize antiretroviral treatment (ART) adherence as well as engagement in HIV care among people living with HIV and substance use disorders. Based on qualitative feedback from providers and patients, we iteratively developed and conducted a proof-of-concept study of a relatively brief transdiagnostic emotion regulation intervention designed to improve ART adherence and engagement in HIV care by addressing behavioral and psychological barriers, including internalized stigma and shame, among people living with HIV and active substance use disorders. The final intervention included 5 individual sessions focused on metacognitive awareness of emotions and thoughts, cognitive reframing of dysfunctional thoughts about the self using concepts such as self-compassion, and identifying and reaching the participants' personalized HIV-self-care goal(s). All participants received daily texts querying current emotion and weekly texts querying ART adherence and substance use. To extend the effects of the intervention, we developed a personalized bidirectional text component through which participants received their personalized compassionate self-statements, informed by the intervention content, in response to their answers to emotion queries for 8 weeks after the 5 sessions. The texts modeled using compassionate self-statements as a form of cognitive reframing, consistent with cognitive restructuring of distorted core beliefs. We consented 10 participants living with HIV and active substance use disorders in the proof-of-concept pilot. Of the 8 participants who completed all intervention sessions, participants replied to 70% of all text messages sent. All 8 reported strong acceptability of the intervention content. This emotion-focused, technology-enhanced intervention demonstrated proof-of-concept, in that this patient population would participate in this intervention. A larger randomized controlled pilot is needed to determine feasibility and acceptability among people living with HIV and substance use disorders, a hard-to-reach and underserved population. Highlights: Stigma interventions to address HIV self-care for substance users are limited. We developed a brief text-enhanced intervention informed by stakeholder feedback. Eight participants completed the intervention, demonstrating proof of concept. Participants indicated the intervention was acceptable and feasible.